Research on the Rock-breaking Characteristics of PDC Cutting Tooth under Combined Axial and Torsional Impact - Wu, Zebing; Zhang, Zihao (Scientific Journal of Technology, 2026)
Aiming at the problems of low rock-breaking efficiency in hard formation and low service life of PDC bits caused by stick-slip vibration of drilling tools, in order to further study the rock-breaking characteristics of PDC cutting teeth and improve their rock-breaking efficiency, based on elastoplastic mechanics and Drucker-Prager rock failure criteria, The ABAQUS/Explicit module was used to establish the interaction model between PDC cutting teeth and rocks under the combined impact of axial torsion. The differences between conventional teeth and axe-shaped teeth in terms of displacement, cutting force, and rock damage history under the combined impact of axial torsion and conventional rock breaking were analyzed, as well as the optimal ratio of different axial torsion impact parameters corresponding to different tooth shapes. The research results show that compared with conventional rock breaking, under the combined impact of axial torsion, the cutting teeth of PDC will have a deeper rock breaking depth, the cutting force will be further reduced, and the time from damage initiation to stripping of the rock unit is less than that of conventional rock breaking. The conventional teeth have the largest rock-breaking volume when the impact amplitude is 4:1 and the impact frequency is 4:1, and the mechanical specific energy is the smallest when the impact amplitude is 4:1 and the impact frequency is 4:1. The volume of rock broken by the axe-shaped teeth is the largest when the impact amplitude is 4:1 and the impact frequency is 4:1. The mechanical specific energy is the smallest when the impact amplitude is 4:1 and the impact frequency is 3:1. It can also be concluded that axe-shaped teeth are more aggressive in rock breaking compared to conventional teeth, and their rock breaking efficiency is higher than that of ordinary teeth. The research results have certain value for improving cutting structure performance and its efficiency of rock crushing.